Hayley Aldridge is still here : a novel - Sloan, Elissa R. (William Morrow, an imprint of HarperCollins Publishers, 2023)
It's been years since anyone really thought about Hayley Aldridge. A child star turned television royalty, Hayley spent years in Hollywood partying and being plastered across the front page of all the tabloids before quietly disappearing after a whirlwind marriage and divorce and very public breakdown. Once the tabloids wrung every last drop out of the drama, they moved on to the next It Girl. But Hayley is still here. For over a decade, she's been trapped in a conservatorship and had every aspect of her life controlled by her parents. She goes nowhere, does nothing without their approval, which is rarely granted. Her visits with her kids are monitored, her fan mail is censored, and she's a prisoner in her own home. She thought things might change once she was well enough to work, but the restrictions got even tighter as she continued to bring money in, the only thing her parents ever really cared about. Hayley is beginning to realize that this nightmare is her actual life. And she's sick of it. When the hashtag #helphayley starts to emerge on social media, and the public starts thinking critically about what happened to her all those years ago, there's finally some momentum on her side. With an upcoming court date to review the status of the conservatorship, Hayley might finally have a chance to break free. But how can she go up against her parents when they're aware of her every move? It's time for Hayley Aldridge to remind the world who she is, this time on her own terms.